Effective stimulating factors for microbial levan production by Halomonas smyrnensis AAD6(T) - TOKSOY ÖNER, EBRU; ARĞA, KAZIM YALÇIN (SOC BIOSCIENCE BIOENGINEERING JAPAN, 2015)
Levan is a bioactive fructan polymer that is mainly associated with high-value applications where exceptionally high purity requirements call for well-defined cultivation conditions. In this study, microbial levan production by the halophilic extremophile Halomonas smyrnensis AAD6(T) was investigated systematically. For this, different feeding strategies in fed-batch cultures were employed and fermentation profiles of both shaking and bioreactor cultures were analyzed. Initial carbon and nitrogen source concentrations, production pH, NaCl and nitrogen pulses, nitrogen and phosphorous limitations, trace elements and thiamine contents of the basal production medium were found to affect the levan yields at different extends. Boric acid was found to be the most effective stimulator of levan production by increasing the sucrose utilization three-fold and levan production up to five-fold. This significant improvement implied the important role of quorum sensing phenomenon and its regulatory impact on levan production mechanism. Levan produced by bioreactor cultures under conditions optimized within this study was found to retain its chemical structure. Moreover, its biocompatibility was assessed for a broad concentration range. Hence H. smyrnensis AAD6(T) has been firmly established as an industrially important resource microorganism for high-quality levan production. (C) 2014, The Society for Biotechnology, Japan. All rights reserved.
Keywords: Levan; Fructan; Halomonas smyrnensis; Exopolysaccharides; Boric acid; Quorum sensing; ZYMOMONAS-MOBILIS; EXTRACELLULAR POLYSACCHARIDE; STRUCTURAL-CHARACTERIZATION; EXOPOLYSACCHARIDES; BACTERIA; EXTREMOPHILES; OPTIMIZATION; CULTURE; STRESS; SIGNAL